2021
DOI: 10.4236/ojacct.2021.102006
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Corporate Governance and Firm Performance: The Effect of Internal Audit and Enterprise Resource Planning (ERP)

Abstract: This research aims to explore the effect of good corporate governance on the performance of listed companies in Saudi Arabia. In particular, the research focuses on the effect of effective internal audit and ERP on corporate governance and, subsequently, firm performance. A questionnaire was used to collect the data. The results indicated that effective corporate governance could be attained by having a good internal audit and ERP system. The results conclude that proper corporate governance positively affects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 28 publications
(31 reference statements)
1
6
0
Order By: Relevance
“…This result supports our first hypothesis, implying that internal audit quality enhances firm performance. This outcome is consistent with the findings of several prior studies (Hutchinson & Zain, 2009;Alflahat, 2017;Bengrich & El Ghadouia, 2020;Alsurayyi & Alsughayer, 2021). The results of model 2 show that internal audit gender moderation with internal audit quality (FCAE*IAFQ) has a positive and significant effect on firm performance (TQ) at the 1% level, implying that the presence of female CAE moderates with the IAF to strengthen Tunisian listed companies' financial performance.…”
Section: Research Model and Variables Definitionsupporting
confidence: 90%
See 1 more Smart Citation
“…This result supports our first hypothesis, implying that internal audit quality enhances firm performance. This outcome is consistent with the findings of several prior studies (Hutchinson & Zain, 2009;Alflahat, 2017;Bengrich & El Ghadouia, 2020;Alsurayyi & Alsughayer, 2021). The results of model 2 show that internal audit gender moderation with internal audit quality (FCAE*IAFQ) has a positive and significant effect on firm performance (TQ) at the 1% level, implying that the presence of female CAE moderates with the IAF to strengthen Tunisian listed companies' financial performance.…”
Section: Research Model and Variables Definitionsupporting
confidence: 90%
“…Moreover, Jiang et al (2020) demonstrated that operations-related services provided by the IAF bring economic benefits to firms and improve operating performance. Along the same lines, Alzeban (2021) and Alsurayyi & Alsughayer (2021) indicated that the implementation of internal audit recommendations (a proxy for effective internal audit) enhances corporate governance and consequently leads to better firm performance in the context of Saudi Arabia. Despite the majority of studies highlighting the positive and significant association between internal audit quality and firm performance, the results of some previous research provide no evidence of this association (Ejoh & Ejom, 2014;Muchiri & Jagongo, 2017;Elewa & El-Haddad, 2019).…”
Section: Background and Hypotheses Developmentmentioning
confidence: 97%
“…Internal audit has always been the last line of defense in the "immune system" of enterprise management [3][4][5] . In order to adapt to the development of the new era, we should use a more systematic and scientific approach, integrate mature big data analysis technology, quickly find the problems and risks arising from enterprise operations, and timely propose solutions [6][7][8] .…”
Section: Value Added Connotation Of Internal Auditmentioning
confidence: 99%
“…On the contrary, Ahmed and Hamdan [65] explores the relationship between corporate governance and firm performance and concludes that the two are unconnected. However, Alsurayyi and Alsughayer [66] examines the impact of corporate governance on firm performance and determines that corporate governance is strongly linked to firm performance. Furthermore, Del Miras-Rodríguez and Martínez-Martínez [67] looked at the impact of good corporate governance on the performance of publicly listed companies, and found that proper corporate governance has a positive impact on firm performance.…”
Section: Corporate Governance and Firm Performancementioning
confidence: 99%